La atención médica de los pacientes con insuficiencia cardíaca: características clínicas, determinantes del pronóstico y seguimiento en la atención primaria - Soriano Palacios, N. (Aten Primaria, 2002)
OBJECTIVE: To assess the process of care and prognosis of patients with heart failure (HF) attended in a tertiary hospital and follow up at the primary care level. DESIGN: Prospective study of 18 months of follow up. SETTING: Tertiary hospital and primary care centers of the reference area. PARTICIPANTS: Patients admitted to a tertiary hospital from the first of july until de 31 of december of 1998. OUTCOME MEASUREMENTS: Pharmacological data and morbimortality at discharge and at the end of the follow-up, functional capacity of survivors. RESULTS: 265 patients were included, with a mean age of 75 years, 57% were females, 73.8% had HF as first diagnosis, 6.1% had MI, and 20% were attended for other medical reasons. The most frequent cause of HF was HTA. Drugs more prescribed at the discharge and follow up were diuretics and ACE inhibitors. Hospital mortality was 6.4% and mortality at the end of the follow-up was 46% (in 77% of those for cardiac reasons). After being discharged 38.5% of the patients were readmitted to the hospital with the diagnosis of HF, 72% were visited by the family physician, 43% at the outpatient clinic and 33% by the cardiologist; 60% of the patients who survived were in I-II NYHA functional class, 76% walked regularly, and 25% did recreational activities and physical exercise. CONCLUSIONS: Patients attended at the hospital with HF are an old population, have frequently associated other chronic diseases, and have a very bad prognosis. These patients spend an important amount of health resources. Drug prescription at the follow up is suboptimum. Patients who survived have an acceptable functional capacity.